A Critical Analysis Of Karl Raimund Popper's Falsification Theory's Thinking Model Philosophy - Asrori, Hilmi; Usman, Usman (ALSYS, 2025)
This article explores the philosophical underpinnings of the falsification theory proposed by Karl Raimund Popper, a key figure in the philosophy of science in the 20th century. Utilizing a library research approach and descriptive analytical methods, the study delves into the core principles and implications of falsification as a model of scientific reasoning. Unlike the verificationist paradigm that seeks to confirm theories through accumulating supportive evidence, Popper’s falsification theory asserts that scientific theories must be testable and open to refutation through empirical observation and experimentation. The article examines how falsification provides a more rigorous framework for distinguishing scientific knowledge from non-scientific claims by promoting continual testing and revision. It further discusses the broader methodological implications of falsification for scientific inquiry, emphasizing its relevance across multiple disciplines. By fostering a mindset of skepticism and critical inquiry, falsification theory challenges researchers to remain open to new evidence and alternative explanations, thereby supporting the evolution of science as a dynamic and self-correcting enterprise. This analysis highlights the enduring importance of Popper’s contribution to research methodology and the development of progressive scientific thought.